Depression, anxiety and acute pain: links and management challenges. Issue 7 (3rd October 2019) - Michaelides, Athena; Zis, Panagiotis
ABSTRACT: Pain is a subjective experience that is influenced by genetics, gender, social, cultural and personal parameters. Opposed to chronic pain, which by definition has to last for at least 3 months, acute pain is mostly because of trauma, acute medical conditions or treatment. The link between mood disorders and acute pain has proven to be increasingly significant since the link is bi-directional, and both act as risk factors for each other. Depression and anxiety are associated with increased perception of pain severity, whereas prolonged duration of acute pain leads to increased mood dysregulation. Although both depression and anxiety have a proven association with acute pain, the link between depression and acute pain is more thoroughly studied. Pain can be the presenting or sole complaint in depressed patients who present to primary care practices and is often overlooked by clinicians. However, reports on the perception of experimentally-induced pain in depressed patients are mixed, showing both an increased and decreased pain threshold and pain tolerance across various studies. Although less data is published about anxiety and pain, the relationship is consistent across studies as increased anxiety leads to increased severity of pain perceived and decreased pain tolerance. Anxiety as well as fear, stress, and catastrophizing are also shown to be mediators in the causal pathway between pain and disability.